Assessing the Use of Oil and Gas Produced Water for Soil Aquifer Treatment in Abu Dhabi - Pavlopoulos, Kosmas (2022)
The United Arab Emirates originally lack for sufficient natural water resources. A major source of water in the UAE is groundwater, which includes water in surface wells that are normally renewed by seasonal rains, and deep wells which are refilled via ancient geological formations. The deficit in water availability due to the increasing demand and shortage in water resources availability can be met by utilizing non-conventional sources such as desalinated water, and recycling wastewater. This paper aims to present a scientific assessment of the possibility of using treated oil and gas-produced water for recharging the underground aquifer in Abu Dhabi through Soil aquifer treatment (SAT). Core samples from the unsaturated zone layers of sand, sandstone, siltstone, and conglomerates layers from the Abu Dhabi area were collected and characterized. Adsorption experiments have been carried out to investigate the capacity of the soil samples for the removal of hazardous contaminants i.e. heavy metals and dissolved organic from synthesized oil-produced water samples. The obtained data were used to calculate the required time for the hazardous contaminants to reach the underground water.